Поливариантный метод кондукционной электротоковой обработки расплава - Цуркин, Н.В.; Иванов, А.В.; Запорожец, Ю.М.; Жданов, А.А.; Честных, Н.В. (My University, 2023)
Изучены перспективы использования в литейном производстве кондукционной электротоковой обработки расплава одновременно несколькими типами тока. Такой принцип в сочетании с различными конструкциями электродных систем позволяет формировать в расплаве поливариантную топологию электромагнитного поля, качественно и количественно по-разному формируя термосиловое нагружение расплава. Для этого найдены условия улучшения показателей качества литого металла. Методами имитационного моделирования найдены варианты обработки, способные активно улучшать инкубационные процессы кристаллизации. Экспериментально подтверждены результаты имитационного моделирования. Установлено, что одновременная обработка двумя типами тока при энергозатратах, которые в 3 раза меньше обработки одним источником тока, на 13% увеличивает временное сопротивление, а относительное удлинение – в 1,5 раза. Относительное сужение образца зафиксировано на уровне 4,4%, что не удается обеспечить для сплава системы Al-Si другими методами обработки. Структура эвтектики модифицирована, зерна α-Al приобретают округлую форму.

The paper describes the features, scientific and practical prospects for the use in the foundry of the conductive electric current treatment of melt by several types of current simultaneously. It is shown that this principle, in combination with various designs of electrode systems, allows to form a polyvariant topology of an electromagnetic field in melt. At the same time, a thermal force loading of melt is formed qualitatively and quantitatively in different ways, which, ultimately, makes it possible to find conditions for improving the quality indicators of a cast metal. The studies were carried out by simulation methods, the results of which showed possible treatment options that can actively improve the crystallization incubation processes. To compare the results of the treatment of the Al-Si alloy melt with one type of the current and simultaneously with two types of current, a physical experiment was carried out, which confirmed the assumptions and simulation results. At the same time, it was found that the simultaneous treatment with two types of current is thrice less costly than the treatment with one current source, increased the tensile resistance by 13%, and the relative elongation by 1.5 times. In this case, a relative narrowing of the sample was recorded at the level of 4.4%, which cannot be provided for this alloy using other methods of melt processing. The structure of the eutectic is actively modified, and α-Al grains acquire a shape close to a round.
Keywords: металлический расплав; электротоковая обработка; варианты воздействия; электродные системы-источники тока; мультифизические процессы; имитационное моделиро- вание; топология полей; физический эксперимент; metal melt; electric current treatment; exposure options; electrode systems – current sources; multiphysical processes; simulation modeling; field topology; physical experiment